2014
DOI: 10.3109/19396368.2014.979513
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic association study ofRNF8andBRDTvariants with non-obstructive azoospermia in the Chinese Han population

Abstract: Increasing evidence indicates that polymorphisms in genes relevant to spermatogenesis might modulate the efficiency of reproduction in men. Ring finger protein 8 (RNF8) and bromodomain testis-specific (BRDT) are two candidate genes associated with spermatogenesis. Here, we considered potential associations of 14 single nucleotide polymorphisms (SNPs) in RNF8 and BRDT genes in Chinese patients with non-obstructive azoospermia (NOA). We analyzed 361 men with NOA and 368 fertile controls by using Sequenom iplex t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, another study that consisted of 276 azoospermic and 182 fertile men of Arab and Jewish descent, demonstrated no association between BRDT rs3088232 and infertility [21]. Another Chinese group analyzed 361 men with non-obstructive azoospermia (NOA) and 368 fertile controls, and they could not find any BRDT variants associated with NOA susceptibility [22]. Thus, the association of BRDT with male infertility is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study that consisted of 276 azoospermic and 182 fertile men of Arab and Jewish descent, demonstrated no association between BRDT rs3088232 and infertility [21]. Another Chinese group analyzed 361 men with non-obstructive azoospermia (NOA) and 368 fertile controls, and they could not find any BRDT variants associated with NOA susceptibility [22]. Thus, the association of BRDT with male infertility is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first to report the upregulation of RNF8 expression using RT-qPCR, However, a microarray study by Spiess et al [31] showed significantly higher expression of RNF8 in individuals with Sertoli cell-only syndrome histology than in men with normal spermatogenesis. Moreover, a haplotype analysis of rs104669 and rs195432 of RNF8, which were in strong linkage disequilibrium, revealed that the AC haplotype was correlated with a reduced risk of NOA and smaller testis volume in a Chinese population [32]. Considering the elevated level of RNF8 expression in the patients with im-paired spermatogenesis in this study, this alteration likely reflects changes in somatic cells, which may imply that RNF8 has potential for interventional therapies [33].…”
Section: Discussionmentioning
confidence: 63%